Project fire : cutting-edge techniques and sizzling recipes from the caveman porterhouse to salt slab brownie s'mores - Raichlen, Steven (Workman Publishing, 2018)
With 100 recipes, this cookbook shows how to put the latest grilling methods to work - from spit-roasting to salt-grilling - using favourite ingredients and adding a dash of daring in flavours, technique, and presentation. Print run 100,000.